The Effect of Lecturer Performance and Learning Creativity on English Learning Achievement of Mercu Buana University Students, Jakarta, Indonesia - Ika Kartika; Saepudin; Junaedi; Anandha Budiantoro; Khaerul Ismed (Jurnal Multidisiplin Madani, 2022)
This study aims to analyze the effect of lecturer performance and learning creativity on English learning achievement of students at Mercu Buana University, Jakarta, Indonesia. This research uses quantitative research methods with survey techniques to answer the hypothesis test that has been formulated. Respondents in this study amounted to 160 students using cluster random sampling technique. Instrument validation of lecturer performance, learning creativity, and English learning achievement used Product-Moment correlation, and reliability was measured by Cronbach Alpha, while hypothesis testing used path analysis. The results of data analysis using path analysis show that (1) there is a direct effect of lecturer performance on English learning achievement, (2) there is a direct effect of learning creativity on English learning achievement, and (3) there is a direct influence of lecturer performance on learning creativity. The implication of this research is that improving English learning achievement can be done through lecturer performance and learning creativity